A synthetic epoxyeicosatrienoic acid analogue prevents the initiation of ischemic acute kidney injury. (2nd June 2019) - Hoff, Uwe; Bubalo, Gordana; Fechner, Mandy; Blum, Maximilian; Zhu, Ye; Pohlmann, Andreas; Hentschel, Jan; Arakelyan, Karen; Seeliger, Erdmann; Flemming, Bert; Gürgen, Dennis; Rothe, Michael; et al.
Abstract: Aim: Imbalances in cytochrome P450 (CYP)‐dependent eicosanoid formation may play a central role in ischemic acute kidney injury (AKI). We reported previously that inhibition of 20‐hydroxyeicosatetraenoic acid (20‐HETE) action ameliorated ischemia/reperfusion (I/R)‐induced AKI in rats. Now we tested the hypothesis that enhancement of epoxyeicosatrienoic acid (EET) actions may counteract the detrimental effects of 20‐HETE and prevent the initiation of AKI. Methods: Male Lewis rats underwent right nephrectomy and ischemia was induced by 45 min clamping of the left renal pedicle followed by up to 48 h of reperfusion. Circulating CYP‐eicosanoid profiles were compared in patients who underwent cardiac surgery with (n = 21) and without (n = 38) developing postoperative AKI. Results: Ischemia induced an about eightfold increase of renal 20‐HETE levels, whereas free EETs were not accumulated. To compensate for this imbalance, a synthetic 14, 15‐EET analogue was administered by intrarenal infusion before ischemia. The EET analogue improved renal reoxygenation as monitored by in vivo parametric MRI during the initial 2 h reperfusion phase. The EET analogue improved PI3K‐ as well as mTORC2‐dependent rephosphorylation of Akt, induced inactivation of GSK‐3β, reduced the development of tubular apoptosis and attenuated inflammatory cell infiltration. The EET analogue also significantly alleviated the I/R‐induced drop in creatinine clearance. Patients developing postoperative AKI featured increased preoperative 20‐HETE and 8, 9‐EET levels. Conclusions: Pharmacological interventions targeting the CYP‐eicosanoid pathway could offer promising new options for AKI prevention. Individual differences in CYP‐eicosanoid formation may contribute to the risk of developing AKI in clinical settings.